2023
DOI: 10.1038/s41563-023-01612-2
|View full text |Cite
|
Sign up to set email alerts
|

Li iontronics in single-crystalline T-Nb2O5 thin films with vertical ionic transport channels

Hyeon Han,
Quentin Jacquet,
Zhen Jiang
et al.

Abstract: The niobium oxide polymorph T-Nb2O5 has been extensively investigated in its bulk form especially for applications in fast-charging batteries and electrochemical (pseudo)capacitors. Its crystal structure, which has two-dimensional (2D) layers with very low steric hindrance, allows for fast Li-ion migration. However, since its discovery in 1941, the growth of single-crystalline thin films and its electronic applications have not yet been realized, probably due to its large orthorhombic unit cell along with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…18 Parkin et al realized the epitaxial growth of single-crystalline T-Nb 2 O 5 thin films with vertical 2D channels, showing a larger and faster resistance change and a wider voltage operation range during Li interaction. 104 Besides, Cui et al first reported the in situ study of the electrochemical generation of sulfur on 2D layered materials, and correlated the varied sulfur states with the corresponding electrochemical behaviors, which shed light on the electrode design for high-performance Li–S batteries. 105…”
Section: Discussionmentioning
confidence: 99%
“…18 Parkin et al realized the epitaxial growth of single-crystalline T-Nb 2 O 5 thin films with vertical 2D channels, showing a larger and faster resistance change and a wider voltage operation range during Li interaction. 104 Besides, Cui et al first reported the in situ study of the electrochemical generation of sulfur on 2D layered materials, and correlated the varied sulfur states with the corresponding electrochemical behaviors, which shed light on the electrode design for high-performance Li–S batteries. 105…”
Section: Discussionmentioning
confidence: 99%
“…Then, anhydrous ethanol was added incrementally following a previously published method. [ 41 ] After micellization, the DCM was removed via rotary evaporation and the resulting kinetically trapped micelle stock had a concentration of 8.53 g mL −1 .…”
Section: Methodsmentioning
confidence: 99%
“…[ 40 ] Similarly, single crystal T‐Nb 2 O 5 thin films were reported to transform reversibly into a monoclinic version and then irreversibly into an amorphous version with progressively higher extents of lithiation. [ 41 ] Such electrochemically induced crystallographic changes are important to understand for the realization of long‐term cycling stability in T‐Nb 2 O 5 electrodes. Herein, the effects of the electrochemical cycling conditions on T‐Nb 2 O 5 capacity retention are examined using CV.…”
Section: Introductionmentioning
confidence: 99%
“…7 An alternative approach involves introducing alkali metal ions, such as Li + , into the ILs to enhance response rates. 17 Ionic gels, created via polymer network gelation in an IL, offer a blend of solid-like stability and IL-like performance, making them suitable for various applications, such as gate electrolytes in thin-film transistors. In this perspective, our primary focus is on ionic-liquid-or ion-gelbased electrolytes, which have demonstrated their effectiveness in numerous recent studies.…”
Section: Electrolytes For Electric Field Gatingmentioning
confidence: 99%